2020
DOI: 10.4269/ajtmh.18-0412
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Enabling Factors Associated with the Implementation of Household Solar Water Disinfection: A Qualitative Study in Northwest Ethiopia

Abstract: Household water treatment including solar disinfection (SODIS) is recognized worldwide as an important intervention for prevention and control of diarrheal and other waterborne diseases. However, in Ethiopia's countryside, SODIS is not being practiced. Therefore, the objective of this qualitative study conducted in villages of Dabat district in northwest Ethiopia was to explore barriers to and enabling factors for consistent and wider implementation of SODIS. This phenomenological study design included four fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(49 reference statements)
0
3
0
2
Order By: Relevance
“…Over all, the low-level practice of household water treatment in the area can be due to psychological factors. Attitude towards water-related technology or behavior is the most important psychological factor to make people treat the drinking water 34 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over all, the low-level practice of household water treatment in the area can be due to psychological factors. Attitude towards water-related technology or behavior is the most important psychological factor to make people treat the drinking water 34 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Over all, the low-level practice of household water treatment in the area can be due to psychological factors. Attitude www.nature.com/scientificreports/ towards water-related technology or behavior is the most important psychological factor to make people treat the drinking water [34][35][36] . This study revealed that safe water storage was significantly associated with health education, health supervision, and family size.…”
Section: Household Water Treatmentmentioning
confidence: 99%
“…Communities' perception of the quality of drinking water is informed by health risk perception, perceived control, past experience, trust on water service provider, influence of impersonal and interpersonal information like media and peers, contextual factors, colour, taste of the water, appearance and demographic variables [15,16]. However, these perceptions are influenced by sociocultural, sociodemographic, and personal experiences and are shaped by service satisfaction, confidence in local and national authorities, selection of the water source as well as beliefs in human control of environment issues and formal and informal flow of information [17]. Community perceptions and practices of health risks related to drinking water are associated with drinking water, the persistence of these health problems and the level of awareness of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse contexto se insere o método Solar Water Desinfection (SODIS), uma técnica desenvolvida para atender populações isoladas e sem acesso a água tratada. Essa técnica consiste em armazenar água em recipientes transparentes de plástico ou vidro, os quais são expostos a luz solar, em intervalos de tempo que variam de 6 a 48 h, dependendo da intensidade da radiação solar e da sensibilidade dos patógenos (McGUIGAN et al, 2012;BITEW et al, 2020). Seu efeito germicida é baseado na combinação de dois fenômenos: o aquecimento térmico e a radiação ultravioleta (UV) (McGUIGAN et al, 2012).…”
Section: Introductionunclassified
“…Segundo esses autores, pela sua simplicidade e baixo custo, o SODIS se popularizou e tem sido disseminado em mais de 50 países da Ásia, América Latina e África, abrangendo uma população superior a 5 milhões de pessoas. Essa técnica pode ser complementada por um tratamento secundário com a utilização de filtros, quando necessário (BITEW et al, 2020).…”
Section: Introductionunclassified